Pengetahuan Petani dalam Berusahatani Sayur Kacang Panjang di Kecamatan Konda Kabupaten Konawe Selatan - Salahuddin, Salahuddin; Mardin, Mardin; Darman, Darman (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This study aims to determine: the level of knowledge of farmers in long bean vegetable farming, long bean vegetable farming activities, and the level of knowledge of farmers associated with long bean vegetable farming activities in the village of Pombulaa Jaya, Konda Sub District, Konawe Selatan District. The sample in this study was determined by simple random sampling. This study uses interval scale analysis and Spearman rank correlation test. The results showed that: the level of knowledge of farmers in farming from long bean vegetable plants in the high category, long bean vegetable farming activities in the medium category, and the level of knowledge of farmers in farming long bean vegetable plants were significantly related to long bean vegetable farming activities in the village Pombulaa Jaya, Konda Sub District, Konawe Selatan District.